Identifying Site-Specific Superoxide and Hydrogen Peroxide Production Rates From the Mitochondrial Electron Transport System Using a Computational Strategy. Issue 6 (20th September 2021) - Duong, Quynh V; Levitsky, Yan; Dessinger, Maria J; Strubbe-Rivera, Jasiel O; Bazil, Jason N
Abstract: Mitochondrial reactive oxygen species (ROS) play important roles in cellular signaling; however, certain pathological conditions such as ischemia/reperfusion (I/R) injury disrupt ROS homeostasis and contribute to cell death. A major impediment to developing therapeutic measures against oxidative stress-induced cellular damage is the lack of a quantitative framework to identify the specific sources and regulatory mechanisms of mitochondrial ROS production. We developed a thermodynamically consistent, mass-and-charge balanced, kinetic model of mitochondrial ROS homeostasis focused on redox sites of electron transport chain complexes I, II, and III. The model was calibrated and corroborated using comprehensive data sets relevant to ROS homeostasis. The model predicts that complex I ROS production dominates other sources under conditions favoring a high membrane potential with elevated nicotinamide adenine dinucleotide (NADH) and ubiquinol (QH2 ) levels. In general, complex I contributes to significant levels of ROS production under pathological conditions, while complexes II and III are responsible for basal levels of ROS production, especially when QH2 levels are elevated. The model also reveals that hydrogen peroxide production by complex I underlies the non-linear relationship between ROS emission and O2 at low O2 concentrations. Lastly, the model highlights the need to quantify scavenging system activity under different conditions to establish a complete picture of mitochondrial ROS homeostasis. In summary, we describe the individual contributions of the electron transport system complex redox sites to total ROS emission in mitochondria respiring under various combinations of NADH- and Q-linked respiratory fuels under varying workloads. Graphical Abstract: